2013
DOI: 10.3389/fnhum.2013.00299
|View full text |Cite
|
Sign up to set email alerts
|

Mom feels what her child feels: thermal signatures of vicarious autonomic response while watching children in a stressful situation

Abstract: Maternal attunement with an infant's emotional states is thought to represent a distinctive feature of the human primary bond. It implies the mother's ability of empathizing with her child in order to fulfil the child's needs in an immediate and appropriate manner. Thus, it is particularly involved in stressful situations. By assuming that maternal attunement embodies a direct sharing of physiological responses with the child, we compared the autonomic response of mothers observing their own distressed child w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
101
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(104 citation statements)
references
References 59 publications
2
101
0
1
Order By: Relevance
“…Temperature fluctuations also indicate participants’ promptness to action. Previous studies have shown significant decreases in nose skin temperature in response to stress-eliciting stimuli in adults, infants, and non-human primates (Kuraoka & Nakamura, 2011; Ioannou et al, 2013; Manini et al, 2013). Therefore, we expected to find only in A carriers exposed to poorer parental behaviors a greater decrease in nose temperature in response to prolonged stress-eliciting stimuli, underlying poorer coping abilities, but we expected a greater increase in nose temperature in response to the same stimuli in A carriers exposed to better parental behaviors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature fluctuations also indicate participants’ promptness to action. Previous studies have shown significant decreases in nose skin temperature in response to stress-eliciting stimuli in adults, infants, and non-human primates (Kuraoka & Nakamura, 2011; Ioannou et al, 2013; Manini et al, 2013). Therefore, we expected to find only in A carriers exposed to poorer parental behaviors a greater decrease in nose temperature in response to prolonged stress-eliciting stimuli, underlying poorer coping abilities, but we expected a greater increase in nose temperature in response to the same stimuli in A carriers exposed to better parental behaviors.…”
Section: Methodsmentioning
confidence: 99%
“…Here we focus on Autonomic Nervous System (ANS) activation to investigate how gene*environment interaction moderates automatic physiological development. We evaluate heart rate changes and peripheral skin temperature (on the nose) to better assess the activation of both the parasympathetic and sympathetic branches of the ANS (Ioannou et al, 2013; Kothgassner et al, 2016; Manini et al, 2013; Quas et al, 2000). …”
Section: Introductionmentioning
confidence: 99%
“…Prior research suggests that physiological synchrony between parents and children is normative (Lunkenheimer, Tiberio, Buss, Boker, & Timpe, 2015). For example, mothers' and children's thermal signatures, a measure of autonomic function, are synchronous while mothers watch their children perform emotionally challenging tasks (Ebisch et al, 2012;Manini et al, 2013). Synchrony in physiological states has been linked to greater behavioral coordination between parents and children; for example, mothers and infants tend to show greater coordination in heart rate during periods of behavioral synchrony, such as gaze sharing (Feldman, Magori-Cohen, Galili, Singer, & Louzoun, 2011).…”
Section: Parent-child Coregulationmentioning
confidence: 99%
“…These researchers found that mothers exposed to their child after the child experienced a stressor exhibited similar facial thermal activity as the child, suggesting autonomic resonance between mother and child even after the offset of the stressful situation. In a related study, these authors found that mothers showed greater and faster contagious responses with their children than women with children who were not their own (Manini et al 2013). Waters and colleagues (2014) followed up on these findings by examining the influence of a mother's stress response on an infant's stress responses after the stressor was terminated.…”
Section: Contagious Stress?mentioning
confidence: 93%